Early Life Predictors of Attention Deficit/Hyperactivity Disorder Symptomatology Profiles from Early Through Middle Childhood - Willoughby, Michael T. (Dev Psychopathol, 2020)
This study used repeated measures data to identify developmental profiles of elevated risk for ADHD (i.e., six or more inattentive and/or hyperactive-impulsive symptoms), with an interest in the age at which ADHD risk first emerged. Risk factors that were measured across the first 3 years of life were used to predict profile membership. Participants included 1,173 children who were drawn from the Family Life Project, an ongoing longitudinal study of children’s development in low-income, nonmetropolitan communities. Four heuristic profiles of ADHD risk were identified. Approximately two thirds of children never exhibited elevated risk for ADHD. The remaining children were characterized by early childhood onset and persistent risk (5%), early childhood limited risk (10%), and middle childhood onset risk (19%). Pregnancy and delivery complications and harsh-intrusive caregiving behaviors operated as general risk for all ADHD profiles. Parental history of ADHD was uniquely predictive of early-onset and persistent ADHD risk, and low primary caregiver education was uniquely predictive of early childhood limited ADHD risk. Results are discussed with respect to how changes to the age of onset criterion for ADHD in DSM5 may impact etiological research and the need for developmental models of ADHD that inform ADHD symptom persistence and desistance.